Oxidative status and vitamin D levels in pregnant women, living in the northern region - S. V. Yakovenko (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2025)
During pregnancy, it is important to maintain the balance of oxidative metabolism to preserve the health of the mother and the unborn child. Gestation induces the process of production of an increased amount of free radicals, which play a role in the formation and differentiation of the placenta, and the antioxidant link of metabolism compensates the oxidative load in the body, controlling oxidative stress. The prevalence of redox processes over antioxidant defence leads to perinatal complications and increased risk of impaired fetal development and neonatal diseases. Vitamin D, whose additional supplementation prevents pregnancy complications, plays an important role in preserving and increasing the antioxidant capacity of the organism.The aim of the study was to determine the level of oxidative stress markers and vitamin D in pregnant women with normal and increased body weight, and to determine their relationship.Object and methods. Vitamin D concentration and the level of thiol status, lipid peroxidation and total antioxidant activity were investigated in 78 pregnant women with normal and overweight and obesity living in Khanty-Mansiysk Autonomous Okrug – Yugra.Results. Physiological values of thiol status and lipid peroxidation indices and increased indices of total antioxidant activity were found in all groups, and intergroup differences were observed. The most pronounced difference between the groups was found in the index of lipid peroxidation, in pregnant women with obesity is higher compared to pregnant women with normal body weight. Vitamin D concentration is below the required level (30 ng/ml) in all groups. The study established a negative relationship between the level of lipid peroxidation and vitamin D, and a positive relationship between body mass index and lipid peroxidation.Conclusion. Obesity affects oxidative metabolism, aggravating free radical oxidation, accompanied by an increase in oxidative stress markers. At the same time, the antioxidant defense system is activated, compensating and counteracting excessive ROS production. The relevance of vitamin D deficiency, as well as its antioxidant properties, has been confirmed. For pregnant women living in the northern region, especially in the presence of pre-gestational excess body weight or obesity, it is necessary to develop a set of preventive measures, including additional intake of vitamin D in a dosage that ensures its physiological level.